2016
DOI: 10.1016/j.egyr.2016.05.006
|View full text |Cite
|
Sign up to set email alerts
|

A multivariate statistical analysis approach to characterize mechanization, structural and energy profile in Italian dairy farms

Abstract: a b s t r a c tThe multivariate statistical approach is one of the most common techniques applied in livestock classification, where quantitative and qualitative variables are used throughout the statistical analysis to obtain farms descriptions. The aim of this study was to divide dairy farms on the bases of farm size, mechanization level, energy profile and availability of building and facilities. A population of 285 conventional dairy cow farms located in the south of Italy was involved in this project. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 11 publications
0
25
0
2
Order By: Relevance
“…It summarized the great number of variables existed in a sample of 963 of buffalo dairy farms. It partitioned them into three clusters to minimize the variance among farms of the same cluster and maximizing the variance among clusters (Todde et al, 2016). From the result, it is concluded that C1 incorporated 53% of the buffalo number kept under the sampled farms, while, the rest, 20% and 27%, were included in C2 and C3, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It summarized the great number of variables existed in a sample of 963 of buffalo dairy farms. It partitioned them into three clusters to minimize the variance among farms of the same cluster and maximizing the variance among clusters (Todde et al, 2016). From the result, it is concluded that C1 incorporated 53% of the buffalo number kept under the sampled farms, while, the rest, 20% and 27%, were included in C2 and C3, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…PCA has been used in Europe, Asia and Africa in the past to classify and differentiate types of smallholder farmers and also to define their development (Alvarez-Lopez et al, 2008;Rao et al, 2014;Robels et al, 2008;Todde et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, it is necessary that the dairy industry improves competitiveness by adopting innovative production processes and improving animal welfare. Improvement and miniaturization of sensors along with continuing costs reduction encourage the implementation of new technologies in dairy farms, allowing increases in their efficiency and productiveness [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%